Student Strategies in Maintaining a Balance Between Academic Work, Organizational Activities, and Personal Life (A Study of Master of Management Students at Pertiba University) - Juhaini Juhaini; Sumiati Sumiati; Juhari Juhari (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2026)
Master's students face high academic demands, involvement in organizational activities, and the need to maintain a balanced personal life. These conditions require effective strategies so that students can perform various roles without causing excessive stress. This study aims to analyze students' strategies in maintaining a balance between academic work, organizational activities, and personal life among Master of Management students at Pertiba University. This study uses a quantitative approach with a survey method by distributing questionnaires to 72 students as respondents. The research variables consisted of student strategies as the independent variable and life balance as the dependent variable. The research instrument was tested for validity and reliability, which showed that all statement items were valid with a calculated r value greater than the table r value (0.232) and reliable with a Cronbach's Alpha value above 0.70. Data analysis techniques included descriptive statistics and linear regression analysis to test the influence between variables. The results of the study indicate that students' strategies fall into the good category, as reflected in their ability to manage time, set priorities, and control academic stress. Students' life balance also falls into the good category, as demonstrated by their ability to complete academic assignments, carry out organizational activities proportionally, and maintain their health and personal lives. The results of the regression analysis show that students' strategies have a significant effect on life balance. These findings indicate that the better the strategies implemented by students, the higher the level of balance between academic, organizational, and personal life demands. This study has important implications for students, study program managers, and educational institutions in designing policies and support programs that encourage the creation of sustainable student life balance. Thus, self-management strategies are a key factor in improving the quality of academic experience and well-being of master's students.